A Strategic Study on Dynamics of Labour Used by Cotton Growers in Gujarat - R. D. Pandya (Indian Journal of Extension Education, 2022)
Cotton enjoys a pre-eminent status among all cash crops in the country.Area-wise India stands first while second as cotton producer throughout the world. The livelihoods of 60 million people of India are depending on cotton cultivation, processing, trade and textiles. Advances in seeds, chemicals and machinery have been allowing the cotton grower to producemore than ever before with less effort. Besides these, the availability of agricultural labour has been shrinked and the skilled labour becomesmore expensive and difficult to obtain.Two talukas and five villages each were identified from nine cotton growing districts of Gujarat. The list of cotton growers who have at least three years of experience of cotton cultivation were obtained from the Talati-cum-Mantri of respective villages. The sample for the study comprised of randomly selected 450 cotton growers and 900 cotton labourers as cotton growers perceived scarcity of labour force during crop protection, weeding and cotton picking. All the cotton growers agreed with increasing labour wages during last five years in all cultural practices particularly in cotton picking, weeding, irrigation and sowing of cotton crop. Low family income, land less, less land for family livelihood and scope ofmore income in cotton cropmotivates the labours of Gujarat towards the cotton farming. Gap between demand and supply of labours, local labours not willing to do work in cotton field and demand of more wages per day were reported by the cotton growers as major constraints during the conduction ofmajor cultural practices of cotton.